E-RETAIL PERCETAKAN ANAMBALEH DESAIN MENGGUNAKAN FRAMEWORK LARAVEL - Dony Novaliendry; Viony Dwiyana Puteri (Universitas Negeri Padang, 2020)
In this 4.0 industrial era, information and communication technology plays a very important role in human life, especially in the trading sector. The pattern of buying and selling is starting to move from the conventional way to be online. Anambaleh Desain is one of the entrepreneurship in the filed printing. Anambaleh Desain requires a website to optimize the product of ordering process and expand its consumer reach. Anambaleh Desain E-retail is made with the MVC (Model View Controller) technique and uses the Laravel Framework which is a framework in the PHP (PHP Hypertext Preprocessor) programming language. The Database Management System used is MySQL. This e-retail aims to optimize the ordering process and transaction in Anambaleh Desain, so that it can provide solution with speed and accuracy in processing and sharing data that has been computerized. It can also minimize the errors in the ordering process and transaction in Anambaleh Desain.